Long term carrying over effects of basic slag, soil aggregate size and groundwater treatments for the reclamation of acid sulfate soils (Bangladesh Journal of Scientific Research, 2018)
A pot experiment was conducted to study the carrying over effects of soil aggregate size, groundwater level and basic slag treatments in acid sulfate soils of Badarkhali and Cheringaseries which were examined for the reclamation during 1998-2001. Initially the soils were very strongly acidic (pH 3.9 for Badarkhali; 3.6 for Cheringa) and very strongly saline (ECe 23 mS/cm for Badarkhali) to moderately saline (10.3 mS/cm for Cheringa). Application of these treatments exerted remarkable improvement in soil fertility and plant growth on these soils after 18 years of occasional cultivation. In 2016, pH at different treatments in these soils ranged from 6.2 to 7.4 for Badarkhali, 5.2 to 7.1 for Cheringa and ECe from 1.7 to 3.2 mS/cm for Badarkhali, 1.5 to 8.75 for Cheringa soils. At the same time in Badarkhali soil, organic matter content (1.3 - 2.8%), total N (0.02 - 0.11%), available N (2.69 - 18.29 mmol/kg), available P (0.78 - 5.08 mmol/kg) were determined and almost similar values of these parameters were recorded in Cheringa soil. Available S contents were found to decrease and ranged from 0.06 - 0.18 cmol/kg in Badarkhali and 0.08 - 0.21 cmol/kg in Cheringa soils. In spite of using basic slag, the concentrations of lead and cadmium in the studied soils were determined below (highest value of Pb was 2.07 mg/kg and Cd 1.8 mg/kg) the normal contents (Pb 70 mg/kg and Cd 10 mg/kg) in the agricultural soils.Bangladesh J. Sci. Res. 30(1&2): 69-79, December-2017